2007
DOI: 10.1097/md.0b013e31815be056
|View full text |Cite
|
Sign up to set email alerts
|

Familial Mediterranean Fever and Cryptogenic Cirrhosis

Abstract: Familial Mediterranean fever (FMF) is a febrile disease characterized by acute, spontaneously resolving episodes of fever and pain caused by serosal inflammation and associated with mutations in the FMF gene, MEFV. Prophylaxis is maintained with colchicine. To our knowledge, no study has yet shown an association between FMF and cirrhosis of the liver. We conducted the current study to describe cryptogenic cirrhosis in FMF and to examine the possible relationship between the 2 entities. Patients with chronic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…In a minority of cases, discontinuation of colchicine will lead to normalisation of the enzyme values, but in most there proves to be no clear association with the drug. Tweezer-Zaks et al , reported that cryptogenic cirrhosis is more common among patients with FMF compared with its prevalence in the general population 56. Rimar et al 57 reported that non-alcoholic cirrhosis is more common in FMF, perhaps as a result of uncontrolled inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…In a minority of cases, discontinuation of colchicine will lead to normalisation of the enzyme values, but in most there proves to be no clear association with the drug. Tweezer-Zaks et al , reported that cryptogenic cirrhosis is more common among patients with FMF compared with its prevalence in the general population 56. Rimar et al 57 reported that non-alcoholic cirrhosis is more common in FMF, perhaps as a result of uncontrolled inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…In this setting, mitochondrial heteroplasmy (variable distribution of weak mitochondria) may play a role in variable organ susceptibility to common oxidative stress [69]. Familial Mediterranean fever has also been reported to be associated with cryptogenic cirrhosis [70], and cryptogenic cirrhosis may also be seen in systemic lupus erythematosus, presumably related to an autoimmune process [71]. We have observed cryptogenic cirrhosis in a 27-year-old male with moderate obesity, type 2 diabetes, late-onset loss of sight and hearing, and chronic renal failure who was subsequently found to suffer Alstrom syndrome (a form of celiopathy) [72,73].…”
Section: What Are We Missing?mentioning
confidence: 98%
“…All patients showed clinical and laboratory improvement upon initiation of colchicine therapy. In addition, nine cases of cryptogenic cirrhosis, cirrhosis without an identifi able cause, were reported in FMF patients by Tweezer-Zaks et al further supporting an association between liver disease and FMF [ 154 ]. Taken together, these fi ndings suggest that FMF should be considered in the differential diagnosis of cryptogenic chronic hepatitis/cirrhosis, especially in regions where this infl ammatory disease is prevalent [ 153 ].…”
Section: Chronic Liver Diseasementioning
confidence: 71%